Multifunctional nanobeacon for imaging Thomsen‐Friedenreich antigen‐associated colorectal cancer. Issue 9 (30th October 2012) - Kumagai, Hironori; Pham, Wellington; Kataoka, Makoto; Hiwatari, Ken‐Ichiro; McBride, James; Wilson, Kevin J.; Tachikawa, Hiroyuki; Kimura, Ryoji; Nakamura, Kunio; Liu, Eric H.; Gore, John C.; Sakuma, Shinji
Abstract This research aimed to validate the specificity of the newly developed nanobeacon for imaging the Thomsen‐Friedenreich (TF) antigen, a potential biomarker of colorectal cancer. The imaging agent is comprised of a submicron‐sized polystyrene nanosphere encapsulated with a Coumarin 6 dye. The surface of the nanosphere was modified with peanut agglutinin (PNA) and poly(N‐vinylacetamide (PNVA) moieties. The former binds to Gal‐β(1‐3)GalNAc with high affinity while the latter enhances the specificity of PNA for the carbohydrates. The specificity of the nanobeacon was evaluated in human colorectal cancer cells and specimens, and the data were compared with immunohistochemical staining and flow cytometric analysis. Additionally, distribution of the nanobeacon in vivo was assessed using an "intestinal loop" mouse model. Quantitative analysis of the data indicated that approximately 2 μg of PNA were detected for each milligram of the nanobeacon. The nanobeacon specifically reported colorectal tumors by recognizing the tumor‐specific antigen through the surface‐immobilized PNA. Removal of TF from human colorectal cancer cells and tissues resulted in a loss of fluorescence signal, which suggests the specificity of the probe. Most importantly, the probe was not absorbed systematically in the large intestine upon topical application. As a result, no registered toxicity was associated with the probe. These data demonstrate the potential use of this novel nanobeacon for imaging the TF antigen as a biomarker for the early detection and prediction of the progression of colorectal cancer at the molecular level.